PENGARUH PEMBELAJARAN PBL BERBASIS MIND MAPPING TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI - Ratnasari, Dwi (Satya Widya, 2022)
The purpose of this study was to analyze the application of the mind mapping-based PBL model to student learning outcomes using Classroom Action Research (CAR) with two cycles with the research sample of all students in class XI IPA 6 SMA Negeri 3 Salatiga consisting of 33 students. This study used a qualitative approach and processed descriptive analysis with research instruments, namely observation sheets and pretest and posttest questions. The results showed an increase in student learning outcomes based on the application of mind mapping-based PBL models in economics subjects. The advice given in this study is that economics teachers can develop PBL models in implementing economic learning.